GABAergic Modulation in Diabetic Encephalopathy-Related Depression - Alberto Yasin Wayhs, Carlos; Maria Tannhauser Barros, Helena; Regla Vargas, Carmen (Current Pharmaceutical Design, 2015)
Central nervous system is not spared from the deleterious effects of diabetes, since several studies have described neuropsychological and neurobehavioral changes in diabetic subjects, suggesting that diabetic encephalopathy should be recognized as a complication of this complex metabolic disorder. In fact, psychiatric manifestations may accompany this encephalopathy, since the prevalence of depression in diabetic patients is much higher than in the general population. Furthermore, evidences from preclinical and clinical studies suggest that GABA plays a role both in the pathophysiology of the diabetic encephalopathy-related depression. So, this review addresses the GABAergic modulation in diabetic encephalopathy-related depression. Data presented from literature support the association between GABA and depressive- like behaviors in diabetic encephalopathy, being this neurotransmitter a potential target for the treatment of diabetes, depression and related comorbidities.
Keywords: insulin